P Pengaruh Edukasi Menstrual Hygiene Menggunakan Video Animasi Terhadap Kesiapan Menghadapi Menarche Pada Siswi di SDN Kaliduren Moyudan Sleman - Titik Endarwati; Farah Salsabila; Atik Badi’ah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Background: Currently, the age of menarche is getting attention because several studies show that there is a decrease in the age of menarche. Indonesia has experienced a decrease in menarche, namely there are 5.2% of children in Indonesia entering menarche under the age of 12 years. This age is entering the early phase of puberty, especially in elementary school children. Poor menstrual hygiene practices will result in susceptibility to disease, this is due to the lack of readiness of female students in facing menarche. This lack of readiness is caused by one of the knowledge factors. The better the knowledge about menstrual hygiene, the better the child will maintain personal hygiene during menstruation, therefore it is important to provide health education / education to children before menarche occurs. Objective: To determine the effect of menstrual hygiene education using animated videos on readiness to face menarche in female students at SDN Kaliduren Moyudan Sleman. Method: This type of research is quantitative with pre-experiment research design and pretest-posttest research design without control group (one group pre-test and post-test without control design). The sample size was 46 respondents with total sampling technique. Data collection using a menarche readiness questionnaire. Data analysis using Wilcoxon test. Results: The results of data processing using the Wilcoxon test obtained p value = 0.000 (p value <0.05), so HA is accepted. Concluison: Menstrual Hygiene education affects the readiness to face menarche in female students at Kaliduren State Elementary School, Moyudan Sleman.